Социология избирательного процесса: проблемы становления - Нельга, А. (Социология: теория, методы, маркетинг, 2000)
Being an institute of real democracy, elections reflect social and economic, cultural,political and legal, as well as national society development. Therefore, electoral process has become an object of sociological research. Formation of separate research direction,named electoral sociology, needs a certain selection of topics related to social contents of elections out of general sociology problems and of political sociology in particular.